Ensino e mercado editorial de livros didáticos de história do Brasil : Rio de Janeiro (1870-1924) - Silva, Alexandra Lima da (2008)
This work analyzes the didactic book elaboration of History of Brazil from the joints between the expansion of education and the publishing market in the city of Rio de Janeiro between 1870 and 1924. Through varied sources, such as proper didactic books, catalogues and registers of publishing companies, programs of education, announcements, periodic and memories, this study search to understand the changes and continuities in the didactic book production of History of Brazil in the bulge of the popularization of the culture scholar and the reading public magnifying in the city. Search to follow the actions of the involved citizens in this process - authors, booksellers, publishers and professors - in search of its motivations and of the multiple involved meanings in the experiences of vulgarization of the historical knowledge through didactic manuals and of the magnifying of formal education.